1984
DOI: 10.1288/00005537-198412000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Primary radiation therapy for juvenile nasopharyngeal angiofibroma

Abstract: Evidence is presented of the effectiveness and relative lack of serious toxicity of external beam megavoltage radiation therapy (RT) as primary treatment for juvenile nasopharyngenl angiofibroma. The importance of careful radiological evaluation of tumor extent prior to irradiation is stressed, and only moderate dose RT is required. Fifty‐five patients have been treated by RT and followed for from 3 to 26 years. Forty‐four of 55 patients (80%) had permanent tumor control following a single course of 3000 cGy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 7 publications
1
87
0
Order By: Relevance
“…Radiotherapy with 35 Gy was administered to case no. 1 post operatively to deal with left out intracranial extension of JNA which slowly regressed there after a period of 1 year [12].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy with 35 Gy was administered to case no. 1 post operatively to deal with left out intracranial extension of JNA which slowly regressed there after a period of 1 year [12].…”
Section: Discussionmentioning
confidence: 99%
“…29 Primary radiation therapy for angiofibroma, at doses of 3000 -3500 cGy, has been considered in a few centres. 27 Recent advancements in technology and techniques have made endoscopic excision of angiofibroma possible. Based on the experience of endoscopic sinus surgery and transnasal endoscopic vidian neurectomy, Kamel first suggested endoscopic transnasal surgery for angiofibroma in 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with intracranial involvement, unresectable disease, religious preferences, or multiple recurrences may be good candidates for radiation treatment [43]. Liu et al [44] reported 2 patients with stage IV incompletely resected tumors who were given 30 Gy and 40 Gy, respectively without recurrent at 1 and 6 years.…”
Section: Radiotherapy For Jnamentioning
confidence: 99%
“…In addition to these risks, panhypopituitarism, temporal lobe necrosis, cataracts and radiation keratopathy may be precipitated by conventional radiation treatment in patients in JNA. Recurrence rate of 20-30% can be expected with radiation treatment alone [1,43,46]. Harwood et al [47] concluded that surgery and radiation carry comparable risks, but that morbidity and mortality risks associated with surgery should be considered.…”
Section: Radiotherapy For Jnamentioning
confidence: 99%